Antimicrobial profiling of coral reef and sponge associated bacteria from southeast coast of India - Rajasabapathy, Raju; Ghadi, Sanjeev C.; Manikandan, Balakrishnan; Mohandass, Chellandi; Surendran, Akhila; Dastager, Syed G.; Meena, Ram M.; James, Rathinam Arthur (2020)
Culturable bacteria associated with marine sponges and coral mucus (collected from Gulf of Mannar and Palk Bay) were screened for their prospective antimicrobial compounds against 9 bacterial pathogens (Bacillus megaterium, B. cereus, Salmonella typhimurium, Staphylococcus aureus, Proteus vulgaris, Klebsillla pneumoniae, Escherichia coli, Pseudomonas aeruginosa and Acinetobacter baumannii) and a fungal pathogen (Candida albicans). Of the 263 bacterial isolates obtained during this study, 52 isolates displayed antimicrobial activity against one or more pathogens. 16S rRNA gene sequencing revealed that these 52 strains affiliated to 14 genera from three phyla Proteobacteria, Firmicutes and Actinobacteria. Sponge associated bacterial strains F-04, 1-23, 1-33 and G-03 inhibited the growth of all the bacterial pathogens tested in this study and significantly the former 2 strains inhibited the growth of fungal pathogen also. Majority of the potential strains (88.4% out of 52 strains) inhibited the growth of Bacillus cereus. Interestingly, an actinomycete strain F-04 (isolated from sponge Orina sagittaria) inhibited the growth of methicillin resistant Staphylococcus aureus. In total, 10 volatile organic compounds were determined from the ethyl acetate and hexane extract of the strain F-04 using GC-MS. Overall, marine bacteria isolated during this study demonstrate the potential for the development of broad spectrum antibiotics.
Keywords: Anti-MRSA; Antimicrobial activity; Bacterial diversity; Coral reef; Sponge